Analisis Kelembagaan Pasar dan Finansial Usaha Ternak Sapi Potong di Kabupaten Lombok Nusa Tenggara Barat - Chairul Muslim (Jurnal Dinamika Sosial Ekonomi, 2004)
During 1997-2001 population of beef cattle farming in Nusa Tenggara Barat (NTB) has decreased 8.8% annually. It was because the number of beef cattle farming was not proportional with the number of its trading. On the other hand the trade of good quality of breeding cattle outer NTB make the population of beef cattle farming decreased. The purpose of this paper to analysis institution market, the role of beef cattle farming on financial aspect and effect of social economics farmer. Base on secunder and primer data this research showed that to increase population of beef cattle farming, industry development in the future in needed. Its mean that goverment must improve previos methode by make any kind policy anfd progamme that can support farmer and another market agent. Furthermore the policy should be abble to keep national cattle resources and to reduce dependently on import in NTB.Keywords: beef cattle farming, market institusion, goverment policy.